From Innovation to Investment: Market-Driven Lessons from AICCRA Zambia Agribusiness Accelerator: Aligning people, systems, and incentives for impact - Kasoma-Pele, W.; Jacobs-Mata, I.; Mutenje, M.; Kakwasha, K. (2026)
AICCRA Zambia Accelerator Program has demonstrated how science-driven innovation can unlock private investment in climate-smart agriculture (CSA) and climate information services (CIS) in the country. The program represents a market-oriented, win–win model in which agribusinesses receive tailored scientific support, while investors gain de-risked, investable SMEs deploying proven technologies. The Accelerator programme was launched in 2022, and by 2025, the program was able to empower 19 SMEs, offering bundled CSA–CIS solutions that directly reached over 718,667 smallholder farmers (43% women). Among all beneficiaries, 184,130 farmers (42% women) reported actively using the CSA and/or CIS technologies made available to them. This represents a 26% adoption rate of AICCRA-supported technologies between 2022 and 2025, demonstrating meaningful uptake and highlighting the relevance, accessibility, and practical value of the promoted innovations in addressing production and climate-related challenges faced by smallholder farmers.